2017
DOI: 10.3347/kjp.2017.55.2.115
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation of Gene Expression in Acanthamoeba castellanii Encystation

Abstract: Encystation mediating cyst specific cysteine proteinase (CSCP) of Acanthamoeba castellanii is expressed remarkably during encystation. However, the molecular mechanism involved in the regulation of CSCP gene expression remains unclear. In this study, we focused on epigenetic regulation of gene expression during encystation of Acanthamoeba. To evaluate methylation as a potential mechanism involved in the regulation of CSCP expression, we first investigated the correlation between promoter methylation status of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Briefly, A. castellanii trophozoites were washed with PBS (pH 7.4) twice, centrifuged at 1,500 rpm for 5 min, and placed into 12-well plates (5×10 5 cells/ml) with encystment medium (95 mM NaCl, 5 mM KCl, 8 mM MgSO 4 , 0.4 mM CaCl 2 , 1 mM NaHCO 3 , 20 mM Tris-HCl, pH 9.0). After induction of cyst formation, all remaining trophozoites were removed by treatment with 0.05% N-lauroylsarcosine sodium salt solution (Sarcosyl; Sigma Chemical Co., St Louis, Missouri, USA) at room temperature for 20 min [17,18].…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, A. castellanii trophozoites were washed with PBS (pH 7.4) twice, centrifuged at 1,500 rpm for 5 min, and placed into 12-well plates (5×10 5 cells/ml) with encystment medium (95 mM NaCl, 5 mM KCl, 8 mM MgSO 4 , 0.4 mM CaCl 2 , 1 mM NaHCO 3 , 20 mM Tris-HCl, pH 9.0). After induction of cyst formation, all remaining trophozoites were removed by treatment with 0.05% N-lauroylsarcosine sodium salt solution (Sarcosyl; Sigma Chemical Co., St Louis, Missouri, USA) at room temperature for 20 min [17,18].…”
Section: Methodsmentioning
confidence: 99%
“…A recent study has revealed that DNA methylation exerts Acanthamoeba encystation, which was delayed by 5-aza-cytidine (5-azaC), a DNA methyltransferase inhibitor. In addition, hypomethylation in the promoter of cyst-specific cysteine proteinase was closely related to its expression level in the Acanthamoeba . A number of reports have demonstrated that histone modifications (or chromatin remodeling) play important roles in the life cycle of several genera of amoeba, including Acanthamoeba , Entamoeba , and Dictyostellium .…”
Section: Discussionmentioning
confidence: 99%
“…This is especially prevalent in parasites, in which epigenetics controls virulence and cell differentiation through regulation of gene expression and thus plays an important role in host-pathogen interaction (e.g., Croken et al, 2012 ; Gomez-Diaz et al, 2012 ). For example, the formation of cysts (an important life cycle stage for host infection) in Toxoplasma (Apicomplexa), Acanthamoeba (Amoebozoa), and Giardia (Excavata) is driven at least partly by epigenetic mechanisms such as histone acetylation and methylation (e.g., H3K18 acetylation and H3R17 methylation in Toxoplasma ; Saksouk et al, 2005 ; Dixon et al, 2010 ; Sonda et al, 2010 ; Moon et al, 2017 ; Lagunas-Rangel and Bermudez-Cruz, 2019 ). Antigenic variation, a strategy used by many pathogens (e.g., Trypanosoma brucei, Giardia lamblia, Giardia doudenalis , and Plasmodium falciparum ) to avoid the host immune system, also is achieved through epigenetic regulation of gene expression (Kulakova et al, 2006 ; Elias and Faria, 2009 ; Juarez-Reyes and Castano, 2019 ; Lagunas-Rangel and Bermudez-Cruz, 2019 ).…”
Section: Epigenetics In Microbial Eukaryotesmentioning
confidence: 99%